2015
DOI: 10.1215/01636545-2799986
|View full text |Cite
|
Sign up to set email alerts
|

“Branded on the Tongue”

Abstract: The laboring population of early modern England (ca. 1550–1750) has long been characterized as “inarticulate”—by contemporary elites and historians alike. This article uses transcribed linguistic exchanges between lower-class speakers and their social superiors—especially those that occurred in the context of the criminal justice system—to reconsider the causes and consequences of plebeian inarticulacy during the period, and beyond. It suggests that certain varieties of inarticulacy—including stammering—should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…For reluctant witnesses having physio‐psychological difficulties when they deposed, see TNA, STAC 5/A45/11; STAC 5/F6/11; STAC 8/239/18. For stammering and social relations, see Taylor, ‘“Branded on the tongue”’.…”
mentioning
confidence: 99%
“…For reluctant witnesses having physio‐psychological difficulties when they deposed, see TNA, STAC 5/A45/11; STAC 5/F6/11; STAC 8/239/18. For stammering and social relations, see Taylor, ‘“Branded on the tongue”’.…”
mentioning
confidence: 99%
“…111 Hillary Taylor suggested that, in their quest for hidden transcripts of rebellion, historians overlook the possibility that people's outer conduct and inner state might be in alignment. 112 Behaving submissively could, in fact, reflect an inner feeling of subordination.…”
mentioning
confidence: 99%
“…Taken together with Williamson and Southard's essay we get the impression of a vibrant and conflicted seventeenth‐century political culture that involved debate and disagreement across the social scale and extended either side of the Civil War years into both local and national politics—and was often centred on forms of middling sociability. Taylor's attention is focused more on the plebeian than the middling, but the emphasis here is not on sedition as a ‘weapon of the weak’ but on the theme of plebeian inarticulacy which is seen as an important facet of subordination in this highly unequal society. Social and economic polarization in the sixteenth and seventeenth centuries led to a pejorative characterization of plebeian speech that reinforced a sense of inferiority, something Taylor sees reflected in the difficulty many plebeians had when trying to speak in the Old Bailey.…”
mentioning
confidence: 99%